The Glenburgh Orogeny as a record of Paleoproterozoic continent-continent collision - Johnson, S.; Sheppard, S.; Rasmussen, Birger; Wingate, M.; Kirkland, C.; Muhling, J.; Fletcher, Ian; Belousova, E (Geological Survey of Western Australia, 2010)
The Gascoyne Province lies at the western end of the Capricorn Orogen, and includes a range of Paleoproterozoic gneisses and metasedimentary basins, known as the Glenburgh Terrane, that are exotic to both the Yilgarn and Pilbara Cratons. Here we present sensitive high-resolution ion microprobe (SHRIMP) U–Pb ages for a variety of detrital zircons and metamorphic zircon and monazite from several of these pre-collisional siliciclastic basins that were deformed and metamorphosed at high metamorphic grade during the Glenburgh Orogeny, when the Yilgarn Craton collided with a previously assembled Pilbara Craton – Glenburgh Terrane. The precursors to the Moogie Metamorphics were deposited sometime between 2240 and 2125 Ma in either a foreland basin to the Ophthalmian Orogeny, or a retro-arc that formed during the collision of the Glenburgh Terrane with the Pilbara Craton. The Quartpot Pelite of the Camel Hills Metamorphics was deposited between 2000 Ma and 1985 Ma as a fore-arc deposit to the Dalgaringa continental margin arc. The Petter Calc-silicate of the Camel Hills Metamorphics was deposited sometime between 2610 and 1965 Ma as part of the Yilgarn Craton passive margin. Metamorphic zircon and monazite ages indicate that continental collision and high-grade metamorphism during the Glenburgh Orogeny (D2g) took place between 1965 Ma and 1950 Ma.